Association of interleukin 22 receptor subunit alpha 1 gene polymorphisms with chronic rhinosinusitis - Dinarte,Vanessa R. Pires (2021)
Abstract Introduction: Chronic rhinosinusitis is a multifactorial disease whose pathogenesis, influenced rhinosinusitis; by both genetic and environmental factors, is still unclear. Previous genetic studies have shown that patients with chronic rhinosinusitis have reduced expression of the Interleukin-22 (IL-22) gene. Objective: Identify and compare the frequency of polymorphisms in the IL22RA1 gene (IL22 alpha-1 subunit receptor) among chronic rhinosinusitis patients – either with or without nasal polyps. Methods: Peripheral blood samples were collected from 70 chronic rhinosinusitis with polyps patients, 14 chronic rhinosinusitis without polyps patients and 68 subjects without chronic rhinosinusitis, followed by DNA extraction and IL22RA1 gene sequence analysis. Results: Among ten polymorphisms identified in the IL22RA1 gene, three were not found in any of the genetic databases analyzed. Chronic rhinosinusitis patients displayed higher frequency of the c.113_114insA frameshift insertion, possibly pathogenic. Conversely, in the control group, polymorphism c.435A > C had a significant predominance of the mutated allele, perhaps related to a potential protection against the chronic rhinosinusitis phenotype. Polymorphism c.770C > T, characterized as a non-synonymous variant, was exclusively found in Black chronic rhinosinusitis with polyps patients. Conclusions: Although no direct causal relationship could be established between IL22RA1 gene polymorphisms and the pathophysiology of chronic rhinosinusitis, genetic variations such as c.113_114insA and c.435A > C may be involved in the susceptibility to or protection against the chronic rhinosinusitis phenotype, respectively. Testing this hypothesis will require studies with larger cohorts.